The Effect of Cash Ratio, Debt to Equity Ratio, Return on Asset, and Total Asset Turnover on Dividend Payout Ratio in IDX-80 Indexed Companies on the Indonesia Stock Exchange - Wakarmamu, Christine M.; Sofiatuzzulfa, Iis (Westscience Press, 2025)
Data for this research were gathered using the documentation study and literature study approaches. The secondary data source was the company's 2022–2024 financial statements, which were made available on the Indonesia Stock Exchange's official website. Both qualitative and quantitative data were used in this research, which also included descriptive statistics, the t test, f test, determination coefficient test, multiple linear regression analysis, ratio analysis methods, and the classical assumption test. In this research, data is handled using the Statistical Program for Social Science (SPSS) version 27. Purposive sampling, which selects samples based on predetermined criteria, is the sampling technique used. According to the preset criteria, the study's sample consists of 20 firms that are listed on the Indonesia Stock Exchange and IDX-80 members. The study's findings show that both the cash ratio and total asset turnover have a significant influence on the dividend payout ratio. This implies that adjustments to these two factors may have an instant impact on how much the business pays out in dividends to its shareholders. Changes in capital structure or asset usage efficiency do not immediately impact the company's dividend distribution policy, as shown by the fact that the Debt-to-Equity Ratio and Return on Asset have no discernible impact on the Dividend Payout Ratio. Concurrently, the Cash Ratio, Debt to Equity Ratio, Return on Asset, and Total Asset Turnover all have a significant influence on the Dividend Payout Ratio, suggesting that these four factors alone may be sufficient to account for differences in the company's dividend distribution strategy.